CSMA como MAC para DWiNoCs - Tesch, Deivid Antunes (2020)
Wireless Network-on-Chip (WiNoC) emerges as one of the most promising tech- nologies to face the scalability problems of conventional NoCs (Network-on-Chip). However, providing multiple and simultaneous access to the shared wireless medium is one of the main challenges of this technology and the use of multiple non-overlapping channels is not a scalable solution due to the limitation of the available bandwidth and of the transceiver complexity. To address this limitation, Directional Wireless Network-on-Chip (DWiNoC) uses another approach that takes advantage of directional antennas characteristics to create multiple non-overlapping channels. However, the media access control mechanism used by DWiNoC is energy inefficient for low traffic loads. Knowing the capacity that CSMA has to deal well with this category of traffic, this work proposes the use of it as a media access control mechanism for DWiNoCs, with the objective of improving channel energy efficiency while maintaining an acceptable level of performance. The use of this mechanism can re- duce, on average, from 39 to 42% the energy consumption of each channel, considering a uniform distribution of the incoming traffic. This, without significantly impacting throughput and latency for inbound traffic loads below 40%.